HUBUNGAN KERAPATAN MANGROVE DAN PRODUKSI SERASAH MANGROVE TERHADAP KELIMPAHAN GASTROPODA DI PERAIRAN DOMPAK TANJUNGPINANG - Supriadi, Agis Dita; Karlina, Ita; Idris, Fadhliyah (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2018)
The purpose of this study is to determine the relationship between mangrove density and mangrove litter production to the abundance of gastropods in Dompak Tanjungpinang waters. This research is done by random sampling method as much as 3 station or 15 plot of quadrant transect with plot size 10x10 m. Collected data is tabulated and grouped by variable type, mangrove density data and mangrove litter production as variable (X) and gastropod abundance as variable (Y). From the results of simple linear regression analysis there is a relationship between mangrove density to gastropod abundance with coefficient value (R2) 0,1756 or 17,56% and relation of mangrove litter production to gastropod abundance with coefficient value (R2) 0,1498 or 14,98% . Sampling of mangroves litter by mounting litter traps measuring 10x10 m. Production of mangrove litter at station I with value 344,253 gbk/100m2/15hari, value at station II is 234,353 gbk/100m2/15hari, and value at station III is 386,574 gbk/100m2/15hari. Factors that affect the high low litter production are mangrove and wind density.